KONSEP ALIENASI CITRA PEREMPUAN DALAM NOVEL AIB DAN NASIB KARYA MINANTO - KHOLIFATUL JANNAH; NOER AINI KARLIA NINGSIH; ABD GHAFUR; MAS ODI MAS ODI (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The novel “Aib dan Nasib” by Minanto depicts the phenomenon of female alienation in a social and cultural context. This study aims to analyze the various forms of alienation experienced by women in the work and to reveal the critical message that the author wants to convey. Using library methods and a feminist approach, this study applies qualitative and hermeneutic analysis to identify the marginalization, stereotypes, and subordination faced by women in the story. The results of the analysis show that female alienation in this novel arises due to unbalanced power relations, patriarchal domination, and social constructions that limit women's roles. All of this simultaneously exposes criticism of gender injustice. Thus, this novel not only depicts the issue of female alienation, but also invites readers to reflect on the position of women in society. This work is an important foundation for further studies on gender issues in Indonesian literature